Improved sample preparation for direct quantitative detection of Escherichia coli O157 in soil using qPCR without pre‐enrichment. Issue 4 (6th June 2017) - Highmore, Callum J.; Rothwell, Steve D.; Keevil, Charles W.
Summary: The prominence of fresh produce as a vehicle for foodborne pathogens such as enterohaemorrhagic Escherichia coli (EHEC) O157 is rising, where disease cases can cause hospitalization and in some cases death. This rise emphasises the necessity for accurate and sensitive methods for detection of pathogens in soil, potential sources of contamination of fresh produce. The complexity of the soil matrix has previously proven prohibitive to pathogen detection via molecular methods without the use of a culture enrichment step, thereby excluding the detection of viable but non‐culturable cells. Here, a sample preparation procedure to facilitate a direct qPCR assay is developed for the detection of E . coli O157 in soil, bypassing culture steps in favour of sample separation through pulsification release and filtration. In sand and peat‐based compost, the method is sensitive to 10 CFU g −1 soil. When testing soils from agricultural sites, it was found that several were qPCR positive for E . coli O157 while being culture‐negative, with peat‐based compost possessing a concentration of 200 tir gene copies per gram. This procedure offers a rapid, quantitative assessment of the potential presence of E . coli O157 in soils which can act as a prescreen of their suitability to grow fresh produce safely. Abstract : Escherichia coli O157 is detected in soil samples using a sample preparation procedure that bypasses culture‐based techniques, in favour of sample separation through use of pulsification release and filtration, and quantification by qPCR. In sand and peat‐based compost, the assay is capable of detecting E . coli O157 to a sensitivity of 10 CFU g −1 . When applied to agricultural soil samples, the assay tested positive for seven of eleven soil samples, despite disparate compositions and geographical origins.